Eksistensi Para “Gus” di Instagram: Visual Semiotik Sebagai Dakwah Baru di Era Digital - al Himni fahma; Mohammad Darwis (Dakwatuna: Jurnal Dakwah dan Komunikasi Islam, 2020)
In the pesantren tradition, whom inherited from the founder of the pesantren to the children and grandchildren are the most eligible decendant . The succession line of relatives under the Kyai who have a young age is pinned as Gus for men and Ning for women. They are a small picture of the behavior of Kyai and the pesantren extended family. The digital age is fostering new roles from new people about a propaganda practice that can break through space and time. The Gus and Ning who occupy the new space maximize the use of social media as kind a step to preach. The new pattern of Da'wah nowadays is very fluid by using artifacts and text from self profiles in the form of audio, images, photos, videos, and writing content. The text is uploaded on their accounts pages periodically and with current typologies. Their existence in a social media Instagram has a different style, modernist and bringing a newness. Visual semiotics is a new way of communicating via technology to the reader (reader) or audience by putting forward text-shaped signs that are verbal (language) and visual. Communication through this sign is presented with a design that contains icons that refer to linguistic messages. Various approaches to preaching communication in a new era, one of them with semiotic visuals on Instagram unlocks visual visions embedded in the icons displayed. All the pictures, photos, and caption notes created by the Gus in their accounts deserve to be elaborated in the context of da'wah in the digital age. Using a purposive sampling technique with a Semiotic Visual analysis, the results show that the variety of sign visualizations on Gus's Instagram account profile means a call for preaching and moral messages in a subtle, dynamic, and open ways. Keywords: Visual, Semiotic, Instagram, Artifacts, Interaction